Implementation of Ambon Banana Peel (Musa Paradisiaca) as Foaming Agent of Banana Fruitghurt using Foam Mat Drying Method - Putry, Cindyana; Paramita, Vita; Hartati, Indah (Vocational College of Universitas Diponegoro, 2022)
Fruitghurt is a product of lactic acid fermentation, namely L. bulgaricus and S. Thermopillus in an acidic state enriched by nutrients from fruit such as Ambon banana but has a short shelf life. Bananas have a role as an additional nutrient in the form of glucose which then becomes a nutrient for lactic acid bacteria. Foam mat drying itself is a drying method that is better than other types of drying because it does not require large production costs and protects the structure of the material through the formation of foam. Application of foam mat drying on fruitghurt using Ambon banana peel extract as a foaming agent is expected to increase the shelf life of fruitghurt as well as an alternative foaming agent derived from vegetable protein Ambon banana peel contains a protein content of about 0.64% when bananas experience a good level of maturity. In the manufacture of fruitghurt powder, the research method used is Response Surface Methodology (RSM) with variables changing the concentration of banana peel extract as a foaming agent, the concentration of maltodextrin as a binder and mixing time. The resulting fruitghurt powder will be analyzed for water content, total acid analysis and pH analysis. The research data were processed using minitab 19 software. The best fruitghurt powder results were found in the 9th variable, namely the minimase variable, where the optimum conditions were banana peel extract concentration of 2.38 ml, maltodextrin concentration of 30 grams and stirring time of 20 minutes. Fruitghurt variable 9 has a pH of 5 after drying which is in accordance with SNI 01-2981-2009, water content is 0.64% and total acid is 1.08%